Routledge companion to intelligence studies - Dover, Robert (Routledge companions., 2014)
This title provides a broad overview of the growing field of intelligence studies, and is essential reading for anyone interested in the subject. Divided into five comprehensive sections, this book provides a strong survey of the cutting edge research in the field of intelligence studies.